Evaluation of cervical smear in high risk women - Pegu, Bhabani; Das, Mukul Chandra; Ali, Javed; Gaur, Bhanu Pratap Singh (International Journal of Research in Medical Sciences, 2017)
Background: Objectives of current study were (i) To find out the pattern of cervical smear in females having risk factors. (ii) To observe the relationship between abnormal cervical smear with high risk factors. Methods:A cross-sectional descriptive study was carried out in the department of obstetrics and gynecology, Guwahati medical college & hospital from July 2009 to August 2010 with the help of Pathology department. 200 women attending gynecological OPD with associated risk factors were selected at random. Detailed history, demographic information, contraceptive history and coital history were taken. Smear was taken from endocervix with the help of Ayer’s spatula or cytobrush. Results:Out of 200 cases, in 110 (55%) the smear was reported negative for malignancy. 73(36.5%) had an inflammatory smear, 11 (5.5%) had CIN, 1(0.5%) had malignancy and 5(2.5%) the smear was inadequate for cytological examination. In the study mean age of Cervical Intraepithelial Neoplasia (CIN) was 42.64 ± 6.34 years. Low socio-economic status, high parity & the use of oral contraceptive pills were major risk factors. Conclusion:Cervical smear should be routinely used as a reliable diagnostic aid for early detection carcinoma cervix especially in high risk cases. The need of the hour is to create awareness and easy accessibility to proper screening.